Characterization of biochar and their influence on microbial activities and potassium availability in an acid soil. Issue 9 (29th July 2019) - Singh, Awtar; Singh, A. P.; Purakayastha, T. J.
ABSTRACT: Application of biochar to soil has increased considerably during recent years because of its effectiveness as a soil amendment causing beneficial effects on soil health. However, the effects have been reported to vary and depend upon types of feedstock and pyrolysis conditions during biochar production. Therefore, characterization of biochar is extremely important for its efficient utilization as a soil amendment. In the present study, biochar was prepared from agro-industrial by-products (rice husk and sugarcane bagasse) and weeds ( Parthenium and Lantana ) under similar pyrolysis conditions. Lantana biochar (LBC) showed the highest pH (10.4) while the lowest value (8.5) being recorded in rice husk biochar (RHBC). The energy-dispersive X-ray spectroscopy (EDS) analysis indicated that LBC and Parthenium biochar (PBC) were superior with respect to potassium (K) content than sugarcane bagasse biochar (SBBC) and RHBC. The Fourier-Transform Infrared Spectroscopy (FTIR) study exhibited the existence of different functional groups in biochar. All the biochar treated soils showed significantly higher microbial activities with different degrees. Application of LBC and PBC at 4.50 g kg −1 soil significantly increased K availability in soil. Lantana biochar and PBC amended the soil at 9 g kg −1 significantly increased the soil pH thus makes these biochar as potential liming materials.